Choroid plexus area and choroid plexus /lateral ventricle area index are potential imaging markers for freezing of gait in Parkinson's disease - Xi Yin; Miao Wang; Fenqiang Zhao; Fengzhu Li; Yuxing Tang; Xiaoyu Wang; Caohui Duan; Song Wang; Yongqin Xiong; Jiarui Yao; Tong Chen; Zhenfu Wang; et al. (Neurobiology of Disease)
Background: The choroid plexus (CP), an important structure involved in cerebrospinal fluid (CSF) circulation, plays a key role in clearing harmful metabolites from the brain. However, the relationship between CP and the development of Parkinson's disease (PD) remains unclear, especially in those with freezing of gait (FOG). We aim to investigate the association between the CP area and CP/lateral ventricle area (CP/Ven) index with clinical symptoms of PD and the development of FOG. Methods: Seventy-three patients with PD (17 with FOG and 56 without FOG) and 49 healthy controls (HCs) underwent 7 T magnetic resonance imaging and neurological assessments. The CP area and CP/Ven index were calculated, and the differences across groups were compared. Spearman's rank correlation was used to evaluate associations between these indices and clinical scales. Binary logistic regression was used to explore the impact of the CP area and CP/Ven index on FOG occurrence in PD. Results: Patients with FOG (PD-FOG) exhibited significantly higher CP area and CP/Ven index than those without FOG (PD-nFOG). Both the CP area and CP/Ven index were positively correlated with the PD motor scale scores, especially postural instability/gait disturbance. Receiver operating characteristic curve analysis showed that the CP area and CP/Ven index effectively distinguished PD-FOG from PD-nFOG, with area under curve of 0.887 and 0.854, respectively. Logistic regression analysis confirmed that both indices independently increased the risk of FOG in PD. Conclusion: Elevated CP area and CP/Ven index are novel, noninvasive neuroimaging markers of FOG in PD.